Tertiary Nasal Syphilis: Rare But Still a Reality - Bipin Kishore Prasad; Suresh Mokamati (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Tertiary syphilis shows most marked manifestations in the nose causing superficial and deep ulcerations and gumma. Gummatous deposit may occur in any portion of the nose. The deformity resulting from the destruction of the bony frame work of the nose and the shrinking of fibroid tissue produces typical saddle nose which is characteristic of syphilis. It is important to establish the diagnosis after carefully ruling out other clinical possibilities and confirming Treponemal infection by laboratory evaluation. The respiratory tract, next to skin, furnishes the most frequent manifestations of syphilis.